Ladies and gentlemen… On your marks, get set, go! About leisure time sport and the popularity of running among men and women - Stempień, Jakub Ryszard (Acta Universitatis Lodziensis. Folia Sociologica, 2015)
This article concerns the case of popularity of running and the dominant participation of men in this sociological phenomenon. Masculinization of the hype for running is mainly visible in case of running competitions open for amateurs (e.g. on a marathon distance) – where men constitute the vast majority of participants. This can be explained with differences in culturebased models of what is masculine and what is feminine. A catalogue of stereotypically masculine features includes, among others, such characteristics as: bravery, toughness and strength. These will correspond not only with the formula of such sports as boxing, wrestling or weightlifting (traditionally considered “masculine”), but also the formula of long-distance running. Participation of men in such competitions can be a confirmation of their own masculinity. In the article the results of own surveys, performed among the participants of DOZ Marathon Lodz with PZU during 2014 and 2015 (sample 2014: N = 1078; sample 2015: N = 1086), are discussed. They document, that for women running is usually only a relatively easy way of caring for their figure and health, while for men it is, in terms of identity, an important field of affirming their masculinity. This is why men more often than women take part in such competitions, spend greater amounts of money on necessary equipment, as well as more frequently join running clubs.